PASAR RAKYAT PONTIANAK TIMUR - Rukiah Rukiah; Yudi Purnomo; Uray Fery Andi (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
The market is a place or area that has existed for a long time as a place to interact in buying and selling to meet needs. The market visually and functionally must be able to provide a sense of comfort and security in the activity. People's Market (public market) has its own characteristics, namely the pattern of interaction between sellers and buyers, such as bargaining between traders and buyers to get a finished price agreement. People's Market (public market) is a common means that must exist in every region. The population of Pontianak city is quite dense, especially in the East Pontianak Subdistrict, Pontianak City. In this region does not have a market that provides complete needs such as Super Market, Public Market and so on. The design of this final task aims to design the concept of a public market area that is easily accessible and can meet the needs of the people in the East Pontianak area and surrounding areas. The scope of the design in this case is to include a fundamental discussion of the design, function of the activities accommodated, supporting facilities and adapted to the design of the public market with current technology. So obtained a concept of The public market area around East Pontianak District that is easily accessible and can meet the needs of the community in the Tanjung Raya 2 road area and surrounding areas.